ANALISIS PENDAPATAN DAN CURAHAN TENAGA KERJA WANITA PADA USAHATANI SAYURAN TERUNG (Solanum melongena L.)DI KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Sriyani Malelak; Marthen R. Pellokila; Made Tusan Surayasa (Undana Press, 2021)
The role of women in family life is growing more widely. One of them is their contribution in improving the family's economy in agriculture, both food crops and horticulture. This study aims to determine; 1) Farmer's income on eggplant vegetable farming in East Kupang District. 2) Contribution of female farm workers in eggplant (Solanum melongena, L) vegetable farming in East Kupang District, and 3) To find out the contribution of female farm workers to eggplant vegetable farming income in East Kupang District. This research uses survey method. The research population is female workers who cultivate eggplant totaling 97 people. The sample size of female workers is 64 people spread over two sample villages, namely 39 people in Oesao Village and 25 people in Pukdale Village. Respondents were randomly assigned by means of a lottery. The data collected was tabulated, and analyzed using simple statistics and then narrated descriptively.The results showed that; 1) The average income received by farmers from eggplant farming in East Kupang District is Rp. 125,355,-/are. 2) The amount of female labor in carrying out eggplant vegetable farming activities in East Kupang District is 119.64 HKO/are, and 3) The contribution of female workers to eggplant vegetable farming income in East Kupang District based on land area is 38.02% (Rp. 47,662,-/are). This means that the outpouring of female labor in East Kupang District is low or small in terms of eggplant vegetable farming income.